USA Public School Educators’ Perceptions of Electronically Delivered Professional Development Modules - McCay, Joel (PAROLE: Journal of Linguistics and Education, 2019)
School meetings, which today are often called teacher workshops are to conduct teacher professional development which may still be desired by today’s teachers. This study was to discover if technological alternatives might be desired by one public school system in the USA. Choices included delivery of professional development via web-based learning material, CD-ROM, and PDF documents as downloadable files for print from the Internet. A questionnaire was designed to find out which media was selected most often for delivery of their own professional development. The study material for this investigation served as professional development modules. Data from surveys were collected to discover why they select them, and whether or not they prefer those modes of professional development to the more traditional modes previously experienced such as teacher meetings/workshops. There were 28 participants in this study. To assess the role of the media for delivery of professional development via learning modules. Descriptive statistics were used to identify demographics and patterns in the educators’ preferences and perceptions. A major conclusion of the study included the medium selected most often was online (82% of respondents)